Utilização de microchips para marcação de pepinos do mar da espécie Holothuria grisea - Souza Júnior, José de (2017)
The management of holothurian fisheries is dependent on more consistent information such as growth and movement of sea cucumbers. However, there is still a gap, the absence of a methodology that allows the marking of sea cucumbers, thus helping capture and recapture studies, which can provide a key to important biological information. The difficulty in marking sea cucumbers is attributed to body elasticity and lack of rigid structures, high probability of marker expulsion, and common occurrences of infection and necrosis around the application area. From this scenario, the present study aimed to test a marking methodology using eugenol as an anesthetic during the application process of microchips in sea cucumbers of the species Holothuria grisea, in order to verify the retention capacity. A total of 100 sea cucumbers of the species H. grisea were collected in Bitupitá, CE and transported to the Aquaculture Biotechnology Center (CEBIAQUA). The animals were placed in a Water Recirculation System (RAS) and kept in quarantine until the experiments were performed. Experiment 1: The animals were divided into two treatments. Treatment without anesthesia (n = 20): animals marked with microchip without anesthetic; Treatment with anesthesia (n = 20): animals anesthetized and labeled with microchip. To perform the marking, 1.2 cm microchips were inserted, with the aid of an applicator, near the oral region of the sea cucumber. The microchip implantation process was followed up using a Logic E GE ultrasound apparatus, with a linear probe of 8 to 13 mhz to avoid insertion of the microchip in the intestine. After the application the animals were observed for six hours to verify retention of the microhcips, after six hours the animals were observed for seven days and counted the body expulsions of the microchips. A second experiment was conducted to verify the movement of the microchip inside the body of the animal, for both two groups of sea cucumbers with five replicates each, treatment without anesthesia and treatment with anesthesia, were placed on an X - ray plate and monitored the Every 10 min for 120 min using an X apparatus with KVP / ME 65, with filter for thoracic vessels and exposure time of 10 seconds. Images were taken every 10 minutes, later with the help of Directiview DR® software the images were processed and analyzed. In the experiment 1 the treatment without anesthesia released the microchips in 2,448 min (+ 1,298.52), while the anesthesia treatment took 6,372 min (+ 3,544,82), with a statistical difference between them. It was observed that the mean velocity of the microchips in the anesthetized animals was 0.0708 mm / min (+ 0.0095), while in the treatment without anesthesia we obtained an average velocity of 0.0633 mm / min (+ 0.0131). Although velocities were similar differences were detected in the distance traveled by the microchip inside the body of the sea cucumber. The microchips covered 73.7% of the body of the sea cucumbers in 120 min in the treatment without anesthetic use, whereas in the anesthetic treatment it only covered 57.81% in the same time interval. Despite the innovative technique used in this research the process was not efficient in marking the sea cucumbers, since all the animals released the microchips after a seven day interval, however it was possible to evaluate the behavior of the animals in the presence of a foreign body Within its organisms, allowing the opening of several hypotheses, thus requiring more research. The methodology employed in this experiment opens the door to short term studies that require markings.